Proceedings of the 10th ACM Conference on Web Science 2019
DOI: 10.1145/3292522.3326038
|View full text |Cite
|
Sign up to set email alerts
|

The Six Relative Advantages in Multichannel Retail for Three-Dimensional Virtual Worlds and Two-Dimensional Websites

Abstract: Multichannel retail is now prevalent with retailers and consumers utilizing a number of channels in parallel or in some instances in an interconnected way. There is a degree of understanding on what each channel can offer but the Relative Advantage of each channel in relation to the others is less understood. This research evaluates the Relative Advantage between the three channels of three-dimensional Virtual Worlds, two-dimensional websites and offline retail stores. The consumer's preferences across the thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The research findings align with existing literature that sees online communities as a form of civic participation, bridging the gap between individual interests and broader societal issues ( Purdy, 2017 ; Lee, 2022 ). Zarifis (2019) results also showed that apart from enjoyment and entertainment, the users value the ability to reinvent yourself, convenience and institutional trust.…”
Section: Discussionmentioning
confidence: 90%
“…The research findings align with existing literature that sees online communities as a form of civic participation, bridging the gap between individual interests and broader societal issues ( Purdy, 2017 ; Lee, 2022 ). Zarifis (2019) results also showed that apart from enjoyment and entertainment, the users value the ability to reinvent yourself, convenience and institutional trust.…”
Section: Discussionmentioning
confidence: 90%
“…As shown by Mancuso et al (2023), metaverse can transform real-economy to a virtual-economy in a very successful manner. Recent studies compared the differences in retail channels when they are offered in three-dimensional virtual world compared to a traditional website (Zarifis, 2019). A similar study in the transformation of an educational environment is currently lacking, and it is important to not only deploy a traditional educational environment in metaverse but also analyze it from multiple viewpoints and relationships to correctly identify its feasibility and effectiveness (Collazos et al, 2007;Xu and Yang, 2024).…”
Section: Research Modelmentioning
confidence: 99%
“…They analyzed the characteristics of various channels, consumer preferences at the purchase stage, differences between simple products and complex products, and the role of trust. Zarifis (2019) evaluated the relative advantages among the 3D virtual world, 2D websites, and offline retail stores, and the results showed participants preferred offline and 2D in most situations. The exceptions were where the Virtual Worlds were preferred, as they provided more enjoyment, entertainment, social shopping, the ability for reinvention, convenience, and institutional trust.…”
Section: Research On the Value Of E-banking Channels And Customer Cha...mentioning
confidence: 99%